How can I help? A less-is-more-approach to responsible, supportive and sustainable, doctoral supervision - Enevold Duncan, Jessica (Högre utbildning, 2024)
The significance of writing for PhD students, particularly at faculties of Humanities, cannot be overemphasized; the written manuscript is the final product to be publicly discussed by external examiners. This article takes as its starting point a “quick & dirty” study of a student-initiated writing group at a humanities department (HD) and the assumption that thesis supervisors nowadays need to take more responsibility for doctoral students’ writing because of existing demands on PhD-students to publish or perish and finish on time (Brodin, 2020). It asks the question how, in times of stress and demands on productivity, increased responsibility may be practiced sustainably in terms of work-load and still benefit students’ development and goals. In other words: How can I, as supervisor, help? What support is needed and how much? The article has as its starting point the experiences and perspectives of the doctoral students and what they think supervisors could do to support. Their answers indicate the significance of minimal intervention and the article discusses the implications and potentials of this: perhaps less is more? Is it enough for supervisors to hold the beacon of vision and purpose in the background? If so, when, and how can this be understood? This article suggests that a less-is-more approach may be implemented as significant non-invasive responsibility and supervisory support, given that there is intentional, collective, mutual awareness and communication among students and supervisor colleagues. The less-is-more approach, as contextualized in this article, is advocated as a sustainable practice, promoting not only self-sufficient successful doctoral students, but a long and healthy work-life and continued careers for students and university teachers alike.